Distance Learning During Covid-19 Pandemic: Students’ Engagement in English Foreign Language Class - Noni Agustina; Ratnawati Susanto; Sri Lestari; Chelsea Chelsea; Yona Yona; Selindah Selindah; Diana Diana (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Purpose - This study aims to explore students’ behaviour, emotional, and cognitive engagement in EFL class during Covid-19 pandemic. Design/methodology/approach - A qualitative approach with class observation, interview, and questionnaire was undertaken to examine the students’ engagement. Teachers and student of two public junior senior high schools in Jakarta, Indonesia involved voluntarily to this study. 5 teachers’ (1 man and 4 women) classes were observed and they were interviewed. 467 (187 male and 280 female) students were administered the questionnaire and 9 of them were interviewed. Findings - The result suggested that the students were disengaged behaviourally, emotionally, and cognitively in English class during distance learning. It occurred due to some factors such as uninteresting learning activities, unstable signal, and lack of students’ understanding. The study provides practical implications for English language teachers. They need to construct the interesting and various learning activities and effective strategies to gain their students’ engagement. Originality/value - Abundance of literatures investigated teaching and learning practices during Covid-19. However, a few studies examined students’ engagement in distance learning. Thus, this study concerned on students’ engagement in EFL class for junior high school level. Paper type – Research paper